Evaluation of an Australian health literacy training program for socially disadvantaged adults attending basic education classes: study protocol for a cluster randomised controlled trial - McCaffery, Kirsten J.; Morony, Suzanne; Muscat, Danielle M.; Smith, Sian K.; Shepherd, Heather L.; Dhillon, Haryana M.; Hayen, Andrew; Luxford, Karen; Meshreky, Wedyan; Comings, John; Nutbeam, Don (BMC public health, 2016)
Background People with low literacy and low health literacy have poorer health outcomes. Literacy and health literacy are distinct but overlapping constructs that impact wellbeing. Interventions that target both could improve health outcomes. Methods/design This is a cluster randomised controlled trial with a qualitative component. Participants are 300 adults enrolled in basic language, literacy and numeracy programs at adult education colleges across New South Wales, Australia. Each adult education institute (regional administrative centre) contributes (at least) two classes matched for student demographics, which may be at the same or different campuses. Classes (clusters) are randomly allocated to receive either the health literacy intervention (an 18-week program with health knowledge and skills embedded in language, literacy, and numeracy training (LLN)), or the standard Language Literacy and Numeracy (LLN) program (usual LLN classes, specifically excluding health content). The primary outcome is functional health literacy skills – knowing how to use a thermometer, and read and interpret food and medicine labels. The secondary outcomes are self-reported confidence, more advanced health literacy skills; shared decision making skills, patient activation, health knowledge and self-reported health behaviour. Data is collected at baseline, and immediately and 6 months post intervention. A sample of participating teachers, students, and community health workers will be interviewed in-depth about their experiences with the program to better understand implementation issues and to strengthen the potential for scaling up the program. Discussion Outcomes will provide evidence regarding real-world implementation of a health literacy training program with health worker involvement in an Australian adult education setting. The evaluation trial will provide insight into translating and scaling up health literacy education for vulnerable populations with low literacy. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12616000213448 .